1979
DOI: 10.1227/00006123-197904000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Experimental Cerebral Edema after Decompressive Craniectomy

Abstract: Decompressive craniectomy has been advocated as a treatment for the cerebral edema associated with massive head injury. Although craniectomy has been successful in lowering intracranial pressure after head injury, a comparison of computerized tomographic scans of comparable patients with traumatic brain edema treated by medical means or decompressive craniectomy showed that bony decompression resulted in apparent exacerbation of edema. To investigate the possibility of enhancement of brain edema by craniectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(40 citation statements)
references
References 0 publications
3
35
0
2
Order By: Relevance
“…Different types of bone decompression have been attempted with variations in the location and size of bone removal depending on the cause of the elevated ICP (1,3,4,5,11,16,17). In a study of 37 STBI patients aged under 40 years, Gaab prospectively performed bilateral DC on 19, and hemicraniectomy on 18 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of bone decompression have been attempted with variations in the location and size of bone removal depending on the cause of the elevated ICP (1,3,4,5,11,16,17). In a study of 37 STBI patients aged under 40 years, Gaab prospectively performed bilateral DC on 19, and hemicraniectomy on 18 patients.…”
Section: Discussionmentioning
confidence: 99%
“…59 Brain edema following decompressive craniectomy has been modeled in animal studies of injury using Evans blue dye extravasation. 15,25,69 Cooper et al 15 found a 7-fold increase in edema formation as determined by Evans blue dye extravasation following craniectomy. Evidence of increased brain edema following craniectomy has not been verified in humans.…”
Section: Perioperative Complicationsmentioning
confidence: 99%
“…By contrast, if decompressive craniectomy is done later-ie, during the stage of vasogenic oedema-it will decrease tissue pressure, drive formation of vasogenic oedema, and thus may have an unintended deleterious effect. 68 Brain imaging may guide the timing of treatment by detecting these stages. Diffusion restriction on MRI correlates with the cytotoxic stage, 10 whereas early hypodensity before mass effect on computed tomography scans may be useful to assess ionic versus vasogenic oedema before decompressive craniectomy.…”
Section: Permeability Poresmentioning
confidence: 99%